Dolphins distributions (Mammalia: delphinidae) in an upwellings zone (Chile) - M. Buscaglia; Walter Sielfeld; Anelio Aguayo‐Lobo (My University, 2020)
The results of a study on sighting frequency and relative abundance of delphinids along the coast of Northern Chile (18°30'S-25°23'S; from coast to 70°27°W), conducted between March and December 2000 in an area of 207.614,60 km2 are reported. The following eight species were sighted: Short-beaked Common Dolphin (Delphinus delphis), Long-beaked Common Dolphin (Delphinus capensis), Short- finned Pilot Whale (Globicephala macrorhynchus), Risso's Dolphin (Grampus griseus), Dusky Dolphin (Lagenorhynchus obscurus), Southern Right Whale Dolphin (Lissodelphis peronii), Striped Dolphin (Stenella coeruleoalba) and Bottlenose Dolphin (Tursiops truncatus). The distribution of dolphins north of Tocopilla showed relationship with the coastal upwelling front of that area, while off the Mejillones Peninsula the relative abundance and diversity of dolphins was associated with the extensive upwelling plume described for this area.
Keywords: Delphinus delphis; Cetacea; Bottlenose dolphin; Beaked whale; Minke whale